Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1365-2249.2007.03479.x
|View full text |Cite
|
Sign up to set email alerts
|

Low mannose-binding lectin (MBL) levels in neonates with pneumonia and sepsis

Abstract: SummaryWe investigated whether deficiency of mannose-binding lectin (MBL), a component of innate immunity, is associated with neonatal pneumonia and sepsis during the first 72 h, i.e. early onset, and during the first month after birth. In 88 neonatal intensive care patients (71 premature), MBL2 genotype and MBL plasma levels at birth were determined prospectively by Taqman analysis and enzyme-linked immunosorbent assay, respectively. Thirty-five neonates (40%) had low, i.e. Յ 0·7 mg/ml, MBL plasma levels at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
2
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 35 publications
7
43
2
14
Order By: Relevance
“…This result somewhat agrees with the result obtained by Ozkan et al [22] who found low producing MBL2 genotypes are significant risk factor for neonatal sepsis in Turkish neonates. Other studies like Frakking et al [27] obtain different results, as they found no relation between the MBL2 gene polymorphism and neonatal sepsis. This discrepancy of results may be explained by different sample size and the variable distribution of MBL2 genotyped in the study population.…”
Section: Discussionmentioning
confidence: 87%
“…This result somewhat agrees with the result obtained by Ozkan et al [22] who found low producing MBL2 genotypes are significant risk factor for neonatal sepsis in Turkish neonates. Other studies like Frakking et al [27] obtain different results, as they found no relation between the MBL2 gene polymorphism and neonatal sepsis. This discrepancy of results may be explained by different sample size and the variable distribution of MBL2 genotyped in the study population.…”
Section: Discussionmentioning
confidence: 87%
“…Low MBL levels in blood from neonates were related to an increased risk of neonatal sepsis and pneumonia (24,25). Cord blood MASP-2 levels tended to be higher for babies with infections (26) and were higher for neonates who developed NEC (17).…”
Section: Lectin Pathway In Critically Ill Childrenmentioning
confidence: 99%
“…The 3 MBL structural variants D, C, and B are associated with an increased risk for meningococcal infections [64,65], pneumonia and sepsis in neonates [66], acute respiratory infections in children [67], hospitalizations due to infections in children [68], recurrent respiratory infections [69], and viral co-infections in adults with pneumococcal pneumonia [70]. Three studies have examined MBL polymorphisms in patients with invasive pneumococcal disease [71][72][73], with one of these three studies finding a significant association.…”
Section: Mannose Binding Lectinmentioning
confidence: 99%